Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Corrigendum to ‘Corenet: A flexible framework for generating and prioritising core cycle network designs’ [Journal of Transport Geography 122 (2026) 104148] - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Corenet: A flexible framework for generating and prioritising core cycle network designs - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Clover in vineyards, a potential trap plant for the mealybug Pseudococcus calceolariae—a vector of GLRaV-3 to grapevines but not clover species - Rebecca Gough; Kar Mun Chooi; Manoharie Sandanayaka; Vicky Davis; Duncan Hedderley; Tara Taylor; Daniel Cohen; Cecilia A. Prator; Rodrigo P. P. Almeida; Vaughn A. Bell; Robin M. MacDiarmid (Journal of Pest Science, 2025)
Grapevine leafroll disease (GLD) affects grapevines worldwide. The primary causal agent of GLD is grapevine leafroll-associated virus 3 (GLRaV-3), which spreads to uninfected grapevines via mealybugs and soft-scale insects. Pseudococcus calceolariae (Hemiptera: Pseudococcidae) is a mealybug vector of GLRaV-3 in New Zealand. P. calceolariae also colonizes clovers ( Trifolium spp.) growing naturally as vineyard ground cover. Separating mealybug from GLRaV-3 grapevine host could be enhanced by a trap plant: an alternative host attractive to and retentive of the target pest. We evaluated the association between P. calceolariae and ‘Grasslands Huia’ white clover (GHWC). GHWC seed was sown under grapevines in a commercial vineyard (14 × 0.4 ha plots); the control was under-vine herbicide use (7 × 0.4 ha plots, where only few Trifolium spp. plants grew). After 2 years, GHWC cover peaked at 40% mealybug infestation in 2019. From 2018 to 2021, P. calceolariae detection and abundance on GHWC was significantly higher than plants from the control plots. There was no treatment effect for mealybug infestation of grapevine leaves nor of GLRaV-3 incidence, independent of vintage. A glasshouse trial found no transmission of GLRaV-3 by P. calceolariae to any of 256 plants among five clover cultivars tested ( Trifolium spp.), including GHWC; mealybug transmitted GLRaV-3 to 35 of 107 Nicotiana benthamiana plants. The results showed that in the 5-year period, added GHWC did not decouple P. calceolariae from the grapevine to reduce GLRaV-3 incidence, but rapid colonization of GHWC by mealybug and the lack of GLRaV-3 transmission to GHWC are encouraging. Further evaluation is needed to assess whether plant biodiversity can benefit a GLRaV-3 ecological management objective.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Woronichinia naegeliana: A common nontoxigenic component of temperate freshwater cyanobacterial blooms with 30% of its genome in transposons - Theo W. Dreher; Robin Matthews; Edward W. Davis; Ryan S. Mueller (Harmful Algae, 2023)

High dimensional model representation for flood fragility analysis of highway bridge - A. Anisha; Deepak Kumar Sahu; Pradip Sarkar; Sujith Mangalathu; Robin Davis (Engineering Structures, 2023)

Patient Engagement: an Assessment of Canadian Radiotherapy Programs’ Current Practices, Perceived Barriers, and Facilitators - Gabrielle Robin; Erika Brown; Carol-Anne Davis; Louise Bird; Lianne Wilson; Ross Halperin; Michael Brundage; Jennifer Croke; Cody Harper; Meredith Giuliani; Amanda Caissie (Journal of Cancer Education, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Complete genome sequence of a novel potyvirus infecting Miscanthus sinensis (silver grass) - Zacharie Leblanc; Marie-Emilie Gauthier; Ruvini Lelwala; Candace Elliott; Cassie McMaster; Robin Eichner; Kevin Davis; Lia Liefting; Jeremy Thompson; Adrian Dinsdale; Mark Whattam; Julie Pattemore; et al. (Archives of Virology, 2022)
Here, we describe the full-length genome sequence of a novel potyvirus, tentatively named “Miscanthus sinensis mosaic virus” (MsiMV), isolated from Miscanthus sinensis (silver grass) held in a post-entry quarantine facility after being imported into Western Australia, Australia. The MsiMV genome is 9604 nucleotides (nt) in length, encoding a 3071-amino-acid (aa) polyprotein with conserved sequence motifs. The MsiMV genome is most closely related to that of sorghum mosaic virus (SrMV), with 74% nt and 78.5% aa sequence identity to the SrMV polyprotein region. Phylogenetic analysis based on the polyprotein grouped MsiMV with SrMV, sugarcane mosaic virus (SCMV), and maize dwarf mosaic virus (MDMV). This is the first report of a novel monopartite ssRNA virus in Miscanthus sinensis related to members of the genus Potyvirus in the family Potyviridae .

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Experimental, numerical and field study investigating a heritage structure collapse after the 2015 Gorkha earthquake - Ashutosh Kumar; Paul N. Hughes; Vasilis Sarhosis; David Toll; Sean Wilkinson; Robin Coningham; Kosh Prasad Acharya; Kai Weise; Annie Joshi; Christopher Davis; Ram Bahadur Kunwar; Prem Nath Maskey (Natural Hazards, 2020)
This paper presents an investigation of the collapse of a 325-year-old multi-tiered heritage temple during the 2015 Gorkha earthquake in Kathmandu, Nepal. The research comprises a reconnaissance survey followed by a geotechnical investigation and numerical back-analysis carried out to understand the potential causes of the collapse. The assessment of the structural configuration of the temple indicated seismic vulnerability in the design due to the presence of discontinuous columns over the height of the temple and age-weakened bonding in the masonry walls. The geotechnical investigation revealed the presence of competent soil strata at the location, assisting the survey which indicated no differential or excessive settlement in the foundation. A series of cyclic triaxial tests were conducted on samples recovered during the geotechnical investigation to determine dynamic behaviour of the soil. Further, dynamic analysis of the plinth of the temple under the recorded acceleration–time history indicated a maximum drift percentage of 1.4% and residual relative displacement of 32 mm suggesting the potential reason behind the collapse. The output of this research will support seismic rehabilitation of ancient structures within World Heritage sites across Nepal and effective action plans to safeguard them against future earthquake hazard.

Experimental assessment of the biosafety of Trissolcus japonicus in New Zealand, prior to the anticipated arrival of the invasive pest Halyomorpha halys - J. G. Charles; G. A. Avila; Kim A. Hoelmer; Sophie Hunt; Robin Gardner-Gee; Frances MacDonald; Vicky Davis (BioControl, 2019)

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Diversity and Plant Pathogenicity of Bursaphelenchus and Related Nematodes in Relation to Their Vector Bionomics - Natsumi Kanzaki; Robin M. Giblin-Davis (Current Forestry Reports, 2018)

Assessing global patterns in mammalian carnivore occupancy and richness by integrating local camera trap surveys - Lindsey N. Rich; Courtney L. Davis; Zach J. Farris; David A. W. Miller; Jody M. Tucker; Sandra Hamel; Mohammad S. Farhadinia; Robin Steenweg; Mario S. Di Bitetti; Kanchan Thapa; Mamadou D. Kane; S. Sunarto; et al. (Global Ecology and Biogeography, 2017)
Aim Biodiversity loss is a major driver of ecosystem change, yet the ecological data required to detect and mitigate losses are often lacking. Recently, camera trap surveys have been suggested as a method for sampling local wildlife communities, because these observations can be collated into a global monitoring network. To demonstrate the potential of camera traps for global monitoring, we assembled data from multiple local camera trap surveys to evaluate the interchange between fine‐ and broad‐scale processes impacting mammalian carnivore communities. Location Argentina, Belize, Botswana, Canada, Indonesia, Iran, Madagascar, Nepal, Norway, Senegal, South Africa, and the U.S.A. Methods We gathered camera trap data, totalling > 100,000 trap nights, from across five continents. To analyse local and species‐specific responses to anthropogenic and environmental variables, we fitted multispecies occurrence models to each study area. To analyse global‐level responses, we then fitted a multispecies, multi‐area occurrence model. Results We recorded 4,805 detections of 96 mammalian carnivore species photographed across 1,714 camera stations located in 12 countries. At the global level, our models revealed that carnivore richness and occupancy within study areas was positively associated with prey availability. Occupancy within study areas also tended to increase with greater protection and greater distances to roads. The strength of these relationships, however, differed among countries. Main conclusions We developed a research framework for leveraging global camera trap data to evaluate patterns of mammalian carnivore occurrence and richness across multiple spatial scales. Our research highlights the importance of intact prey populations and protected areas in conserving carnivore communities. Our research also highlights the potential of camera traps for monitoring wildlife communities and provides a case study for how this can be achieved on a global scale. We encourage greater integration and standardization among camera trap studies worldwide, which would help inform effective conservation planning for wildlife populations both locally and globally.

Who has ‘Dibs!’ on a dead rhinoceros beetle? - Robin M. Giblin‐Davis (Environmental Microbiology, 2017)

Multiplication factor for open ground storey buildings–a reliability based evaluation - D. C. Haran Pragalath; Bhosale Avadhoot; Davis P. Robin; Sarkar Pradip (Earthquake Engineering and Engineering Vibration, 2016)

Evaluation of Project Students are Sun Safe (SASS): A University Student-Delivered Skin Cancer Prevention Program for Schools - Raeann Davis; Lois J. Loescher; Jillian Rogers; Denise Spartonos; Aimee Snyder; Stephanie Koch; Robin B. Harris (Journal of Cancer Education, 2015)

Dynamic firing properties of type I spiral ganglion neurons - Robin L. Davis; Robert A. Crozier (Cell and Tissue Research, 2015)

Calibration of a hysteretic model for glass fiber reinforced gypsum wall panels - Maganti Janardhana; P. Robin Davis; S. S. Ravichandran; A. M. Prasad; D. Menon (Earthquake Engineering and Engineering Vibration, 2014)

The release and unsuccessful establishment of the Melaleuca biological control agent Fergusonina turneri and its mutualistic nematode Fergusobia quinquenerviae - Paul D. Pratt; Scott Blackwood; Susan A. Wright; Matthew Purcell; Min B. Rayamajhi; Robin M. Giblin-Davis; Sonja J. Scheffer; Philip W. Tipping; Ted D. Center (BioControl, 2013)

The relationship between knowledge of family history and cancer characteristics at diagnosis in women newly-diagnosed with invasive breast cancer - Marijana Lijovic; Susan R. Davis; Pam Fradkin; Jo Bradbury; Maria La China; Max Schwarz; Rory Wolfe; Helen Farrugia; Robin J. Bell (Familial Cancer, 2009)